Development and Characterization of Alginate Based Biocomposite Films Reinforced by Gracilaria Powder. Issue 1 (November 2021) - Fransiska, D; Basriman, I; Falafi, A R; Priambudi, P; Nurhayati; Agusman
Abstract: The edible film is a thin sheet that functions as a coating or packaging material on foods that may be eaten simultaneously as packaged products. The ingredient that is often used is alginate made from seaweed. The advantage of using seaweed as a bioplastic material is that it can be produced in a large quantity, low price, and is non-toxic; it can also produce bioplastic that resembles conventional plastic. The experimental method with two components of Completely Randomized Factorial Design was employed in this study (CRFD), the concentration of Gracilaria seaweed powder with four levels (0%, 0.5%, 1%, 1.5%, and 1%) and concentration of alginate with three levels (1%, 1.25%, dan 1.5%). The result showed that the concentration of seaweed powder and concentration of alginate that used in the making of the edible film had a significant effect on the quality of the edible film on all parameters, which is thickness, moisture content, tensile strength, elongation, water vapor transmission rate, water-solubility, color, opacity and surface morphology. There is an interaction between the concentration of seaweed powder and concentration of alginate at the significant effect on the quality of the edible film, which is a concentration of seaweed powder at the level of 1.5% and concentration of alginate at the level of 1.5%. The film has a the thickness of 0.25mm, moisture content of 6.94%, tensile strength of 54.29 Mpa, elongation of 3.26%, the water solubility of 64.41%, water vapor transmission rate of 3242 g/cm 2 /24 h, and opacity of 81.7%.